The Influence of Festival Attractiveness at the Sagarurung Festival on Tourists’ Decision to Visit Penukal Abab Lematang Ilir (PALI) (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
This study aims to analyze the influence of festival attractiveness at the Sagarurung Festival on tourists’ decision to visit Penukal Abab Lematang Ilir (PALI) Regency. The study employed a quantitative approach with an associative research design, involving 100 respondents who had previously attended the festival, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that festival attractiveness, consisting of festival atmosphere, social interaction, cultural symbols, and festival activities, was generally perceived positively by visitors. The dimensions of festival atmosphere and cultural symbols had a positive influence on the decision to visit, while social interaction and festival activities showed a negative but insignificant effect. The coefficient of determination (R²) of 6.2% suggests that other factors outside the model have a more dominant influence. Nevertheless, tourists demonstrated a high level of interest in visiting and revisiting the destination. This study highlights the importance of improving event quality and integrating external factors in the development of tourism strategies.